Exploring the linkage between workplace precaution measures, covid-19 fear and job performance: The moderating effect of academic competence - Chaudhry, Naveed Iqbal; Rasool, Samma Faiz; Raza, Masooma; Mohelska, Hana; Rehman, Fazal ur (Springer, 2023)
The coronavirus disease 2019 (Covid-19) has created emerging mental health challenges around the world. Like other countries, Pakistan is also confronted with covid-19 calamities. The aim of the study is to examine the impacts of workplace measures (WM) on the job performance (JP) and covid-19 fears (CF) along with the moderating role of academic competence (AC) based on the organizational support theory (OST) and job demand and resources (JDR) theory. A quantitative approach was applied to collect data from 333 banking employees in Gujranwala (Pakistan), and the hypothesis were tested via structural equation modeling using SPSS and AMOS. The study findings indicate that workplace measures significantly affect covid-19 fears except for individual preventive measures (IPM). Similarly, workplace measures significantly impact on job performance apart from information about the pandemic (IAP). Moreover, academic competence insignificantly moderates between workplace measures and covid-19 fears, but a significant moderation is found between information about pandemic (IAP) and covid-19 fears. Meanwhile, academic competence significantly moderates between workplace measures and job performance instead of a relationship between information about pandemic and job performance. However, this study was limited only to the banking sector of Pakistan. So, it will open the doors for future researchers to investigate other cultural contexts and sectors. This research gives a holistic understanding of workplace measures and contributes to the body of knowledge by enlightening the moderating role of academic competence in the banking sector of Pakistan. These useful insights would enable practitioners and policy makers to develop more efficient strategies and workplace measures to enhance job performance and reduce the fears of covid-19 among employees.
Zkoumání spojení mezi preventivními opatřeními na pracovišti, strachem z covid-19 a pracovním výkonem: zmírňující účinek akademické kompetence
Keywords: Workplace measures; Covid-19 fear; Job performance; Academic competence; Opatření na pracovišti; strach z Covid-19; Pracovní výkon; Akademická kompetence